Canadian Health Measures Survey: Brief Overview - Tremblay, Mark S. (Can J Public Health, 2007)
The Canadian Health Measures Survey (CHMS) was developed to address important data gaps and limitations in existing health information by collecting directly measured indicators of health and wellness on a representative sample of approximately 5,000 Canadians aged 6–79 years. The CHMS includes an in-home general health interview and a subsequent clinic visit where direct physical measures of health are taken (anthropometry, spirometry, blood pressure, fitness, physical activity, oral health examination, blood and urine specimens) in mobile clinics. Reference laboratories are used to analyze biological specimens for indicators of general health, chronic disease, infectious disease and environmental biomarkers and to store biospecimens for future research. This paper provides a brief overview of the survey sampling, methodological, operational, logistical, ethical, legal and social issues and procedures related to the CHMS.